Cats Felis catus as a threat to bats worldwide: a review of the evidence. (15th February 2021) - Oedin, Malik; Brescia, Fabrice; Millon, Alexandre; Murphy, Brett P.; Palmas, Pauline; Woinarski, John C.Z.; Vidal, Eric
Abstract: Cats Felis catus, in all their forms (domestic, free‐roaming/stray and feral), have been identified as a major global threat to biodiversity, especially birds and small mammals. However, there has been little previous consideration of the extent and impact of predation of bats by cats, or of whether specific characteristics make certain species of bats particularly vulnerable to predation by cats. We reviewed the impact of cats on bats, based on a collation of scientific literature and the International Union for Conservation of Nature (IUCN) Red List database. Our aim was to produce a synthesis of the extent to which cats prey upon and threaten bats. We also collated available data on cat diet, which provide information on predation rates of bats by cats. Few studies ( n = 44) have identified bat species preyed upon or threatened by cats, with a disproportionate number of studies from islands. In these studies, 86 bat species (about 7% of the global extant tally) are reported as preyed upon or threatened by cats, and about one quarter of these species are listed as Near Threatened or threatened (IUCN categories Critically Endangered, Endangered, or Vulnerable). In IUCN Red List assessments, cats are more frequently mentioned as a threat to threatened or Near Threatened bat species than to non‐threatened species (IUCN category Least Concern). In studies reporting on the incidence of bats in cat dietary samples (scats, stomachs and guts), the frequency of occurrence of bats in samples averaged 0.7 ± 2.1% (mean ± standard deviation; n = 102). Many studies had sample sizes that were too small to be likely to detect bats. All forms of cat are reported to kill bats, and such predation has been reported in all major terrestrial habitats. We conclude that predation by cats is an under‐appreciated threat to the world's bat species. Abstract : Cats Felis catus, in all their forms (domestic, free‐roaming/stray and feral), have been identified as a major global threat to biodiversity. However, the threat that cats cause to bats has not yet been assessed. We reviewed the impact of cats on bats, based on a collation of scientific literature and the IUCN Red List database, to produce a synthesis of the extent to which cats kill bats and threaten their populations. We found that 86 bat species (about 7% of the global extant tally) are killed or threatened by cats, and about one quarter of these species are listed as Near Threatened, Vulnerable, Endangered, or Critically Endangered on the IUCN Red List. Pet, stray and feral cats all kill bats, and such predation has been reported in all major terrestrial habitats, natural and anthropized. We conclude that predation by cats is an under‐appreciated threat to the world's bat species. Abstract : RESUMÉ EN FRANÇAIS Les chats Felis catus, sous toutes leurs formes (domestiques, errants ou harets), ont été identifiés comme une menace mondiale majeure pour la biodiversité, en particulier pour les oiseaux et les petits mammifères. Cependant, l'ampleur de ce phénomène et l'impact de la prédation exercée sur les chauves‐souris par les chats n'ont guère été pris en compte jusqu'à présent. En particulier la question de savoir si des caractéristiques spécifiques rendent certaines espèces de chauves‐souris particulièrement vulnérables à la prédation par les chats reste en suspens. Nous avons examiné l'impact des chats sur les chauves‐souris, en croisant les informations issues de la littérature scientifique sur le sujet et celles disponibles dans la base de données de la liste rouge de l'Union Internationale pour la Conservation de la Nature (UICN). Notre objectif était de produire une synthèse mondiale visant à estimer dans quelle mesure les chats s'attaquent aux chauves‐souris et constituent une menace. Nous avons également rassemblé les données disponibles sur le régime alimentaire des chats, qui fournissent des informations sur les taux de prédation des chauves‐souris par les chats. Peu d'études ( n = 44) ont permis d'identifier des espèces de chauves‐souris prédatées et/ou menacées par les chats, un nombre disproportionné d'entre elles concernent les écosystèmes insulaires. Ces études ont permis d'identifier 86 espèces de chauves‐souris (environ 7 % des espèces mondiales) représentant des proies ou étant directement menacées par les chats ; environ un quart de ces espèces sont classées comme "quasi menacées" ou "menacées" (catégories de l'UICN : En danger critique d'extinction, En danger ou Vulnérable). Dans les évaluations de la Liste rouge de l'UICN, les chats sont plus fréquemment mentionnés comme une menace pour les espèces de chauves‐souris menacées ou quasi menacées que pour les espèces non menacées (catégorie de l'UICN "Préoccupation mineure"). Dans les études analysant le régime alimentaire des chats (excréments, estomacs et tubes digestifs) la fréquence d'occurrence des chauves‐souris dans les échantillons était en moyenne de 0.7 ± 2.1 % (moyenne ± écart‐type ; n = 102). Dans de nombreux travaux, la taille des échantillons était trop petite pour permettre de détecter la prédation sur des chauves‐souris. Toutes les formes de chats s'attaquent aux chauves‐souris, et cette prédation a été signalée dans tous les principaux habitats terrestres. En conclusion, la prédation des chauves‐souris par les chats apparait être une menace sous‐estimée au niveau mondial.